MXene / CNTs self-assembled conductive rubber and preparation method thereof

Through electrostatic self-assembly technology, Mxene and CNTs are self-assembled in a whisker-like layered manner to form a conductive filler network and mixed with the rubber matrix liquidly, solving the problem of insufficient sensitivity, stability and durability of conductive rubber, and achieving high sensitivity and good conductivity.

CN119912738APending Publication Date: 2025-05-02CHINA PETROLEUM & CHEMICAL CORP +1

Patent Information

Application Number
CN202311431839.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-31
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The existing conductive rubbers have shortcomings in terms of sensitivity, stability and durability, and the assembly effect of MXene and CNTs is not ideal, resulting in easy damage to the conductive film.

Method used

Through electrostatic self-assembly technology, the processed two-dimensional MxeneTi3C2Tx nanosheets are self-assembled in a whisker-like layered manner to form a good conductive filler network, and are mixed with the rubber matrix in liquid phase to form a highly sensitive conductive rubber.

Benefits of technology

The sensitivity, stability and durability of conductive rubber are improved, and the deformation of 1% can be detected. The construction of the conductive network improves the transmission of electrons in the rubber matrix and has a good reinforcement effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119912738A_ABST
    Figure CN119912738A_ABST
Patent Text Reader

Abstract

The invention relates to MXene / CNTs self-assembled conductive rubber and a preparation method thereof, and belongs to the technical field of conductive rubber. Through treatment, the CNTs have positive electricity and can be subjected to electrostatic self-assembly with MXene with negative electricity, the assembled conductive filler can be further assembled with latex particles of rubber through electrostatic interaction, the conductive filler and the latex particles are gelatinized together to prepare conductive rubber, and the conductive functional filler can form a good conductive network in a rubber matrix, so that the conductivity of the conductive rubber is improved. Therefore, the sensitivity, the stability and the durability of the conductive rubber are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a MXene / CNTs self-assembled conductive rubber and a preparation method thereof, belonging to the technical field of conductive rubbers. Background Art

[0002] Conductive rubber can convert mechanical signals into recordable electrical signals and has excellent stretchability. It is increasingly used in personalized healthcare monitoring, electronic skin, human-machine interfaces, and soft robots, and has therefore attracted much attention.

[0003] Among them, conductive rubber is obtained by blending conductive fillers (MXene, CNTs, etc.) and rubber matrix. However, most of the current research is to simply blend conductive fillers with elastomer matrix, or to reduce the percolation threshold by increasing the compatibility with elastomer by grafting silane coupling agent, and the resulting conductive rubber does not form a more complete conductive network. The insufficiency of this conductive network greatly limits the sensitivity, stability and durability of conductive rubber. In order to improve the conductive network, a method of hybridization between different fillers is often used. In the patent publication number CN111223587A, MXene and CNTs are simply combined to obtain a dendritic layered self-assembled flexible conductive film, and MXene and CNTs are not processed, the assembly effect is not ideal, and the conductive film is easily damaged by the external environment. So far, there is no report on the application of MXene and CNTs electrostatic self-assembled fillers in rubber latex for building a conductive filler network in a rubber matrix. Summary of the invention

[0004] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a MXene / CNTs self-assembled conductive rubber and a preparation method thereof, so as to improve the sensitivity, stability and durability of the conductive rubber.

[0005] The present invention is achieved by adopting the following technical solutions:

[0006] The present invention provides a method for preparing a MXene / CNTs self-assembled conductive rubber, comprising the following steps:

[0007] S1, 2D MxeneTi3C2T x Preparation of nanosheets

[0008] Etching Ti3C2T using etching solution x The etched liquid was filtered with deionized water until the pH of the washing liquid was neutral, and then ultrasonically dispersed with deionized water, centrifuged to obtain the supernatant, and freeze-dried to obtain the two-dimensional MxeneTi3C2T x Nanosheets, spare;

[0009] S2. Treatment of carbon nanotubes (CNTs)

[0010] A certain mass of carbon nanotubes is dispersed in a mixture of ethanol and water, tetraethyl orthosilicate and a compound having both hydroxyl and amino groups are slowly added dropwise to the mixture, and the mixture is stirred in a water bath; the mixture of ethanol and water is filtered and washed to remove impurities and unreacted compounds, and the mixture is vacuum dried for standby use;

[0011] S3, MXene and CNTs electrostatic self-assembly

[0012] Take a certain amount of the two-dimensional MxeneTi3C2T in step S1 x The nanosheets are dispersed in water, and the treated carbon nanotubes CNTs in step S2 are dispersed in a mixture of ethanol and water; the two-dimensional MxeneTi3C2T x The nanosheets and the treated carbon nanotubes CNTs are ultrasonically treated, and then stirred and mixed in a water bath to obtain whisker-like layered self-assembled MXene / CNTs fillers, which are then filtered and vacuum dried for later use;

[0013] S4. Preparation of flexible conductive rubber

[0014] A certain amount of the self-assembled MXene / CNTs filler in step S3 is stirred and dispersed in the rubber latex, ultrasonicated, then stirred in a water bath, and then demulsified with a demulsifier. After vacuum drying, a conductive rubber raw rubber is obtained, and then a certain amount of zinc oxide, stearic acid, sulfur and accelerator are added for mixing. Finally, the mixed rubber is vulcanized to obtain a conductive rubber.

[0015] Through treatment, CNTs with positive charge can be electrostatically self-assembled with MXene with negative charge. The assembled conductive filler can be further assembled with rubber latex particles through electrostatic action and gelled together to prepare conductive rubber. The conductive functional filler can form a good conductive network in the rubber matrix, thereby improving the sensitivity, stability and durability of the conductive rubber.

[0016] Preferably, the etching solution in step S1 comprises HCl and LiF, HCl, LiF and Ti3C2T x The mass ratio is 9:4:2.5.

[0017] Preferably, in the mixed solution of step S2, the mass ratio of ethanol to water is 4:1, and the mass ratio of carbon nanotubes to the mixed solution is 1:(10-20).

[0018] Preferably, the compound having both hydroxyl and amino groups in step S2 is any one or more of 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, hydroxyethylethylenediamine and 2-hydroxyethylethylenediamine; and the mass ratio of carbon nanotubes, tetraethyl orthosilicate and the compound having both hydroxyl and amino groups in step S2 is 1:(0.2-0.5):(0.1-0.25).

[0019] Preferably, the mass ratio of ethanol to water in the mixed solution of step S3 is 1:4, and the mass ratio of two-dimensional Mxene Ti3C2Tx nanosheets to carbon nanotubes CNTs is 1:(3-5).

[0020] Preferably, in step S3, the two-dimensional MxeneTi3C2T x The ratio of nanosheets to water is 1:(10-20); in step S3, the ratio of carbon nanotubes CNTs to ethanol / water is 1:(5-10).

[0021] Preferably, the mass ratio of the self-assembled MXene / CNTs filler to the rubber in step S4 is 1:(3-20); the rubber latex in step S4 is any one of styrene-butadiene rubber latex, natural rubber latex, epoxy natural rubber latex, nitrile rubber latex and carboxylated nitrile rubber latex.

[0022] Preferably, in step S4, the mass ratio of rubber, zinc oxide, stearic acid, sulfur and accelerator is 1:(0.03-0.05):(0.02-0.03):(0.02-0.04):(0.02-0.04).

[0023] Preferably, in step S4, the accelerator is one or more of N-tert-butyl-2-benzothiazole sulfenamide, N,N-tetramethyl dithiodithioamide, N-cyclohexyl-2-benzothiazole sulfenamide, and 2-mercaptobenzothiazole.

[0024] The present invention also provides a MXene / CNTs self-assembled conductive rubber, which is prepared according to the above-mentioned MXene / CNTs self-assembled conductive rubber preparation method.

[0025] The MXene / CNTs self-assembled conductive rubber prepared by the present invention has improved sensitivity, stability and durability.

[0026] The beneficial effects achieved by the present invention are:

[0027] 1. The MXene / CNTs self-assembled conductive rubber prepared by the present invention is a highly sensitive flexible conductive rubber that can detect a deformation of 1%, greatly broadening the application range of the conductive rubber.

[0028] 2. The present invention electrostatically self-assembles two-dimensional structured Mxene and carbon nanotubes CNTs to achieve the preparation of whisker-like layered fillers, and the assembled conductive fillers can electrostatically adsorb latex particles, greatly improving the construction of the conductive network in the rubber matrix, facilitating the transmission of electrons in the rubber matrix, and having a good reinforcement effect.

[0029] 3. The whisker-like structure of the self-assembled filler of the present invention can be regulated by the treatment of CNTs and the mass ratio of MXene to CNTs in the present invention, without the need for expensive equipment and harsh conditions, and is simple to operate and has the potential for large-scale production.

[0030] 4. The conductive rubber prepared by the present invention uses liquid phase mixing of conductive fillers and rubber, which is different from the traditional dry mixing method, greatly reduces the generation of dust in the production process and meets the concept of green production. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a scanning electron microscope image of the MXene / CNTs self-assembled filler obtained by the ratio of Example 1 of the present invention;

[0032] Figure 2 This is a scanning electron microscope picture of the dispersion of MXene / CNTs self-assembled filler in emulsion polystyrene-butadiene rubber obtained by the ratio of Comparative Example 1 of the present invention;

[0033] Figure 3 This is a graph showing the resistance variation of the MXene / CNTs self-assembled conductive rubber obtained by the ratio in Example 1 of the present invention as the strain increases;

[0034] Figure 4 This is the strain-resistance change diagram of the MXene / CNTs self-assembled conductive rubber after 2000 repetitions according to the ratio of Example 1 of the present invention;

[0035] Figure 5 This is a resistance change diagram of the MXene / CNTs self-assembled conductive rubber obtained by the ratio of Example 1 of the present invention and Comparative Examples 1 and 2 under 1% strain. DETAILED DESCRIPTION

[0036] To clearly illustrate the solution in the present invention, further description is given below in conjunction with the accompanying drawings:

[0037] The present invention discloses a method for preparing a MXene / CNTs self-assembled conductive rubber, comprising the following steps:

[0038] S1. Preparation of two-dimensional MxeneTi3C2Tx nanosheets

[0039] Etching Ti3C2Tx powder with an etching solution, stirring and etching for 48 hours at 25-28°C, filtering the etched liquid with deionized water until the pH of the washing liquid is neutral, then ultrasonically dispersing with deionized water, centrifuging to obtain the supernatant, and freeze-drying for 45h-50h to obtain a two-dimensional MxeneTi3C2Tx nanosheet for use;

[0040] S2. Treatment of carbon nanotubes (CNTs)

[0041] A certain amount of carbon nanotubes are dispersed in a mixture of ethanol and water, and tetraethyl orthosilicate and a compound having both hydroxyl and amino groups are slowly added to the mixture, and stirred for 6-10 hours in a water bath at 55-65°C; the mixture of ethanol and water is filtered and washed to remove impurities and unreacted compounds, and dried in a vacuum drying oven at 85-95°C for 3.5-4.5 hours for use;

[0042] S3, MXene and CNTs electrostatic self-assembly

[0043] A certain amount of the two-dimensional MXeneTi3C2Tx nanosheets of step S1 are dispersed in water, and the treated carbon nanotubes CNTs of step S2 are dispersed in a mixed solution of ethanol and water; the two-dimensional MXeneTi3C2Tx nanosheets and the treated carbon nanotubes CNTs are respectively ultrasonicated at 23-27°C for 18-22min, and then stirred and mixed in a water bath at 38-42°C for 1.5-2h to obtain whisker-like layered self-assembled MXene / CNTs fillers, which are filtered and dried in a vacuum oven at 88-92°C for 7.5-8.5h for standby use;

[0044] S4. Preparation of flexible conductive rubber

[0045] Take a certain amount of the self-assembled MXene / CNTs filler in step S3 and stir and disperse it in the rubber latex, ultrasonicate it at 22-27°C for 20-40min, then stir it in a water bath at 58-62°C for 1.5-2h, then use a demulsifier to demulsify it, and dry it in a vacuum oven at 88-92°C for 3.5-4.5h to obtain a conductive rubber raw rubber, then add a certain amount of zinc oxide, stearic acid, sulfur and accelerator to mix it, and finally vulcanize the mixed rubber at 165-175°C for 9-11min to obtain a conductive rubber.

[0046] Example 1

[0047] This embodiment 1 provides a method for preparing a MXene / CNTs self-assembled conductive rubber, comprising the following steps:

[0048] S1, 2D MxeneTi3C2T x Preparation of nanosheets

[0049] 2.5g Ti3C2T was etched using 9g HCl (8mol / L) and 4g LiF etching solution. x The powder was stirred and etched at 25-28 ° C for 48 hours, and the etched liquid was filtered with deionized water until the pH of the washing liquid was neutral, and then ultrasonically dispersed with deionized water, centrifuged to obtain the supernatant, and freeze-dried for 48 hours to obtain a two-dimensional MxeneTi3C2T x Nanosheets, spare.

[0050] S2. Treatment of carbon nanotubes (CNTs)

[0051] Take 2g of carbon nanotubes and disperse them in a mixture of 20g of ethanol and water, with a mass ratio of ethanol to water of 4:1. Slowly drop 0.8g of tetraethyl orthosilicate and 0.4g of 3-aminopropyltrimethoxysilane into the mixture, and stir for 6h in a 60℃ water bath. Use the mixture of ethanol and water to filter and wash to remove impurities and unreacted compounds, and dry in a vacuum oven at 90℃ for 4h for later use.

[0052] S3, MXene and CNTs electrostatic self-assembly

[0053] Take 1g of the 2D MxeneTi3C2T from step S1 x The nanosheets were dispersed in 10 g of water, and 3 g of the treated carbon nanotubes CNTs in step S2 were dispersed in a mixture of 15 g of ethanol and water, with the mass ratio of ethanol to water being 1:4. x The nanosheets and treated carbon nanotubes CNTs were ultrasonicated at 25°C for 20 min, and then stirred and mixed in a 40°C water bath for 1.5 h to obtain whisker-like layered self-assembled MXene / CNTs fillers, which were filtered and dried in a vacuum oven at 90°C for 8 h for use.

[0054] S4. Preparation of flexible conductive rubber

[0055] Take 3g of the self-assembled MXene / CNTs filler in step S3 and stir and disperse it in 270g of latex polystyrene butadiene rubber emulsion with a rubber content of 22%, ultrasonicate it at 25°C for 20min, then stir it in a water bath at 60 for 1.5h, then use a demulsifier to demulsify it, dry it in a vacuum oven at 90°C for 4h to obtain a conductive rubber raw rubber, then add 2g of zinc oxide, 1.5g of stearic acid, 1.5g of sulfur and 1.5g of N-tert-butyl-2-benzothiazolesulfonamide for mixing, and finally vulcanize the mixed rubber at 170°C for 10min to obtain a conductive rubber.

[0056] Example 2

[0057] S1, 2D MxeneTi3C2Tx Preparation of nanosheets

[0058] This embodiment is the same as step S1 in embodiment 1.

[0059] S2. Treatment of carbon nanotubes (CNTs)

[0060] Take 4g of carbon nanotubes and disperse them in a mixture of 80g of ethanol and water, with a mass ratio of ethanol to water of 4:1. Slowly drop 2g of tetraethyl orthosilicate and 1g of 3-aminopropyltriethoxysilane into the mixture, and stir for 6h in a 60℃ water bath. Use the mixture of ethanol and water to filter and wash to remove impurities and unreacted compounds, and dry in a vacuum oven at 90℃ for 4h for later use.

[0061] S3, MXene and CNTs electrostatic self-assembly

[0062] Take 1g of the 2D MxeneTi3C2T from step S1 x The nanosheets were dispersed in 10 g of water, and 5 g of the treated carbon nanotubes CNTs in step S2 were dispersed in a mixture of 50 g of ethanol and water, with the mass ratio of ethanol to water being 1:4. x The nanosheets and treated carbon nanotubes CNTs were ultrasonicated at 25°C for 20 min, and then stirred and mixed in a 40°C water bath for 1.5 h to obtain whisker-like layered self-assembled MXene / CNTs fillers, which were filtered and dried in a vacuum oven at 90°C for 8 h for use.

[0063] S4. Preparation of flexible conductive rubber

[0064] This embodiment is the same as step S4 in embodiment 1.

[0065] Example 3

[0066] S1. Preparation of two-dimensional Mxene Ti3C2Tx nanosheets

[0067] This embodiment is the same as step S1 in embodiment 1.

[0068] S2. Treatment of carbon nanotubes (CNTs)

[0069] Take 20g of carbon nanotubes and disperse them in a mixture of 100g of ethanol and water, with a mass ratio of ethanol to water of 4:1. Slowly drop 10g of tetraethyl orthosilicate and 4g of hydroxyethylethylenediamine into the mixture, and stir for 6h in a 60℃ water bath. Use the mixture of ethanol and water to filter and wash to remove impurities and unreacted compounds, and dry in a vacuum oven at 90℃ for 4h for later use.

[0070] S3, MXene and CNTs electrostatic self-assembly

[0071] Take 1g of the 2D MxeneTi3C2T from step S1 x The nanosheets were dispersed in 10 g of water, and 20 g of the treated carbon nanotubes CNTs in step S2 were dispersed in a mixture of 200 g of ethanol and water, with the mass ratio of ethanol to water being 1:4. x The nanosheets and treated carbon nanotubes CNTs were ultrasonicated at 25°C for 20 min, and then stirred and mixed in a 40°C water bath for 1.5 h to obtain whisker-like layered self-assembled MXene / CNTs fillers, which were filtered and dried in a vacuum oven at 90°C for 8 h for use.

[0072] S4. Preparation of flexible conductive rubber

[0073] This embodiment is the same as step S4 in embodiment 1.

[0074] Example 4

[0075] S1, 2D MxeneTi3C2T x Preparation of nanosheets

[0076] This embodiment is the same as step S1 in embodiment 1.

[0077] S2. Treatment of carbon nanotubes (CNTs)

[0078] This embodiment is the same as step S2 in embodiment 1.

[0079] S3, MXene and CNTs electrostatic self-assembly

[0080] This embodiment is the same as step S3 in embodiment 1.

[0081] S4. Preparation of flexible conductive rubber

[0082] Take 3g of the self-assembled MXene / CNTs filler in step S3 and stir and disperse it in 41g of latex polystyrene butadiene rubber emulsion with a rubber content of 22%, ultrasonicate it at 25°C for 20min, then stir it in a water bath at 60 for 1.5h, then use a demulsifier to demulsify it, dry it in a vacuum oven at 90°C for 4h to obtain a conductive rubber raw rubber, then add 0.27g zinc oxide, 0.18g stearic acid, 0.18g sulfur and 0.18g 2-mercaptobenzothiazole for mixing, and finally vulcanize the mixed rubber at 170°C for 10min to obtain a conductive rubber.

[0083] Example 5

[0084] S1, 2D MxeneTi3C2T x Preparation of nanosheets

[0085] This embodiment is the same as step S1 in embodiment 1.

[0086] S2. Treatment of carbon nanotubes (CNTs)

[0087] This embodiment is the same as step S2 in embodiment 1.

[0088] S3, MXene and CNTs electrostatic self-assembly

[0089] This embodiment is the same as step S3 in embodiment 1.

[0090] S4. Preparation of flexible conductive rubber

[0091] This embodiment is the same as step S4 in embodiment 1, except that 100 g of latex polybutadiene styrene rubber emulsion with a rubber content of 50% is used.

[0092] Example 6

[0093] S1, 2D MxeneTi3C2T x Preparation of nanosheets

[0094] This embodiment is the same as step S1 in embodiment 1.

[0095] S2. Treatment of carbon nanotubes (CNTs)

[0096] This embodiment is the same as step S2 in embodiment 1.

[0097] S3, MXene and CNTs electrostatic self-assembly

[0098] This embodiment is the same as step S3 in embodiment 1.

[0099] S4. Preparation of flexible conductive rubber

[0100] This embodiment is the same as step S4 in embodiment 1, except that 100 g of natural rubber latex with a rubber content of 40% is used.

[0101] Example 7

[0102] S1, 2D MxeneTi3C2T x Preparation of nanosheets

[0103] This embodiment is the same as step S1 in embodiment 1.

[0104] S2. Treatment of carbon nanotubes (CNTs)

[0105] This embodiment is the same as step S2 in embodiment 1.

[0106] S3, MXene and CNTs electrostatic self-assembly

[0107] This embodiment is the same as step S3 in embodiment 1.

[0108] S4. Preparation of flexible conductive rubber

[0109] This embodiment is the same as step S4 in embodiment 1, except that 100 g of nitrile rubber latex with a rubber content of 30% is used.

[0110] Example 8

[0111] S1, 2D MxeneTi3C2T x Preparation of nanosheets

[0112] This embodiment is the same as step S1 in embodiment 1.

[0113] S2. Treatment of carbon nanotubes (CNTs)

[0114] This embodiment is the same as step S2 in embodiment 1.

[0115] S3, MXene and CNTs electrostatic self-assembly

[0116] This embodiment is the same as step S3 in embodiment 1.

[0117] S4. Preparation of flexible conductive rubber

[0118] This embodiment is the same as step S4 in embodiment 1, except that 100 g of carboxylated nitrile rubber emulsion with a rubber content of 30% is used.

[0119] Comparative Example 1

[0120] Take 10g of pure CNTs filler and stir and disperse it in 270g of latex polystyrene butadiene rubber emulsion with a rubber content of 22%, ultrasonically treat it at 25°C for 20min, then stir it in a water bath at 60 for 1.5h, then use a demulsifier to demulsify it, and dry it in a vacuum oven at 90°C for 4h to obtain a conductive rubber raw rubber, then add 2g of zinc oxide, 1.5g of stearic acid, 1.5g of sulfur and 1.5g of N-tert-butyl-2-benzothiazolesulfonamide for mixing, and finally vulcanize the mixed rubber at 170°C for 10min to obtain vulcanized rubber.

[0121] Comparative Example 2

[0122] Take 10g of pure MXene filler and stir and disperse it in 270g of latex polystyrene butadiene rubber emulsion with a rubber content of 22%, ultrasonically treat it at 25°C for 20min, then stir it in a water bath at 60 for 1.5h, then use a demulsifier to demulsify it, and dry it in a vacuum oven at 90°C for 4h to obtain a conductive rubber raw rubber. Then, add 2g of zinc oxide, 1.5g of stearic acid, 1.5g of sulfur and 1.5g of N-tert-butyl-2-benzothiazolesulfonamide for mixing. Finally, the mixed rubber is vulcanized at 170°C for 10min to obtain vulcanized rubber.

[0123] Table 1 Performance test data

[0124]

[0125] The data in Table 1 show that the conductive rubber prepared based on the MXene / CNTs self-assembled conductive rubber preparation method has excellent sensitivity, stability and durability thanks to the good conductive network constructed by the self-assembled filler in the rubber matrix.

[0126] Of course, the above contents are only preferred embodiments of the present invention and cannot be considered to limit the scope of the embodiments of the present invention. The present invention is not limited to the above examples, and equal changes and improvements made by ordinary technicians in the technical field within the essential scope of the present invention should all fall within the scope of the patent coverage of the present invention.

Claims

1. A method for preparing MXene / CNTs self-assembled conductive rubber, characterized in that: The following steps are involved: S1, 2D MxeneTi3C2T x Preparation of nanosheets Etching Ti3C2T using etching solution x The etched liquid was filtered with deionized water until the pH of the washing liquid was neutral, and then ultrasonically dispersed with deionized water, centrifuged to obtain the supernatant, and freeze-dried to obtain the two-dimensional MxeneTi3C2T x Nanosheets, spare; S2. Treatment of carbon nanotubes (CNTs) A certain mass of carbon nanotubes is dispersed in a mixture of ethanol and water, tetraethyl orthosilicate and a compound having both hydroxyl and amino groups are slowly added dropwise to the mixture, and the mixture is stirred in a water bath; the mixture of ethanol and water is filtered and washed to remove impurities and unreacted compounds, and the mixture is vacuum dried for standby use; S3, MXene and CNTs electrostatic self-assembly Take a certain amount of the two-dimensional MxeneTi3C2T in step S1 x The nanosheets are dispersed in water, and the treated carbon nanotubes CNTs in step S2 are dispersed in a mixture of ethanol and water; the two-dimensional MxeneTi3C2T x The nanosheets and the treated carbon nanotubes CNTs are ultrasonically treated, and then stirred and mixed in a water bath to obtain whisker-like layered self-assembled MXene / CNTs fillers, which are then filtered and vacuum dried for later use; S4. Preparation of flexible conductive rubber A certain amount of the self-assembled MXene / CNTs filler in step S3 is stirred and dispersed in the rubber latex, ultrasonicated, then stirred in a water bath, and then demulsified with a demulsifier. After vacuum drying, a conductive rubber raw rubber is obtained, and then a certain amount of zinc oxide, stearic acid, sulfur and accelerator are added for mixing. Finally, the mixed rubber is vulcanized to obtain a conductive rubber.

2. The method for preparing the MXene / CNTs self-assembled conductive rubber according to claim 1, characterized in that: The etching solution in step S1 includes HCl and LiF, HCl, LiF and Ti3C2T x The mass ratio is 9:4:2.

5.

3. The method for preparing the MXene / CNTs self-assembled conductive rubber according to claim 1, characterized in that: The mass ratio of ethanol to water in the mixed solution of step S2 is 4:1, and the mass ratio of carbon nanotubes to the mixed solution is 1:(10-20).

4. The method for preparing the MXene / CNTs self-assembled conductive rubber according to claim 1, characterized in that: In the step S2, the compound having both hydroxyl and amino groups is any one or more of 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, hydroxyethylethylenediamine and 2-hydroxyethylethylenediamine; in the step S2, the mass ratio of carbon nanotubes, tetraethyl orthosilicate and the compound having both hydroxyl and amino groups is 1:(0.2-0.5):(0.1-0.25).

5. The method for preparing the MXene / CNTs self-assembled conductive rubber according to claim 1, characterized in that: The mass ratio of ethanol to water in the mixed solution of step S3 is 1:4, and the two-dimensional MxeneTi3C2T x The mass ratio of nanosheets to carbon nanotubes CNTs is 1:(3-5).

6. The method for preparing the MXene / CNTs self-assembled conductive rubber according to claim 1, characterized in that: In the step S3, the ratio of the two-dimensional Mxene Ti3C2Tx nanosheets to water is 1:(10-20); in the step S3, the ratio of the carbon nanotubes CNTs to ethanol / water is 1:(5-10).

7. The method for preparing the MXene / CNTs self-assembled conductive rubber according to claim 1, characterized in that: The mass ratio of the self-assembled MXene / CNTs filler to the rubber in step S4 is 1:(3-20); the rubber latex in step S4 is any one of styrene-butadiene rubber latex, natural rubber latex, epoxy natural rubber latex, nitrile rubber latex and carboxylated nitrile rubber latex.

8. The method for preparing the MXene / CNTs self-assembled conductive rubber according to claim 1, characterized in that: In step S4, the mass ratio of rubber, zinc oxide, stearic acid, sulfur and accelerator is 1:(0.03-0.05):(0.02-0.03):(0.02-0.04):(0.02-0.04).

9. The method for preparing MXene / CNTs self-assembled conductive rubber according to claim 1, characterized in that: In the step S4, the accelerator is one or more of N-tert-butyl-2-benzothiazole sulfenamide, N,N-tetramethyl dithiodithioamide, N-cyclohexyl-2-benzothiazole sulfenamide, and 2-mercaptobenzothiazole.

10. A MXene / CNTs self-assembled conductive rubber, characterized in that: Prepared according to the method for preparing MXene / CNTs self-assembled conductive rubber according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Dendritic layered self-assembled flexible conductive film and preparation method thereof

    CN111223587A

Cited By

  • Conductive latex, preparation method thereof and application of conductive latex in labor protection gloves

    CN121343255A

  • Conductive latex, method for its preparation and use in safety gloves

    CN121343255B